Anisotropic shock responses of nanoporous Al by molecular dynamics simulations. - Xia Tian; Kaipeng Ma; Guangyu Ji; Junzhi Cui; Yi Liao; Meizhen Xiang (PLoS ONE, 2021)
Mechanical responses of nanoporous aluminum samples under shock in different crystallographic orientations (<100>, <111>, <110>, <112> and <130>) are investigated by molecular dynamics simulations. The shape evolution of void during collapse is found to have no relationship with the shock orientation. Void collapse rate and dislocation activities at the void surface are found to strongly dependent on the shock orientation. For a relatively weaker shock, void collapses fastest when shocked along the <100> orientation; while for a relatively stronger shock, void collapses fastest in the <110> orientation. The dislocation nucleation position is strongly depended on the impacting crystallographic orientation. A theory based on resolved shear stress is used to explain which slip planes the earliest-appearing dislocations prefer to nucleate on under different shock orientations.